Cross‐linked ultra‐high‐molecular‐weight polyethylene prepared by silane‐induced cross‐linking under in situ development of water. Issue 8 (16th April 2018) - Li, Qiuying; Chen, Tenghui; Sun, Lewen; Guo, Weihong; Wu, Chifei
Abstract: This work aimed at providing a suitable method for preparing the cross‐linked ultra‐high‐molecular‐weight polyethylene (UHMWPE). First, UHMWPE was grafted with a silane compound using organic peroxide as an initiator in the molten state. Then, cross‐linking was performed by compression molding of the mixture of the silane‐grafted UHMWPE and CaC2 O4 ·H2 O. Water released from CaC2 O4 ·H2 O made the silane‐grafted UHMWPE cross‐link. In particular, no catalyst was added in the cross‐linking step. Fourier Transform Infrared results confirmed that the silane has been grafted onto the UHMWPE chain successfully and the grafting index varied with the dosage of the initiator. With the increasing of CaC2 O4 ·H2 O content, the gel ratio increased and average molecular weight of the cross‐linked UHMWPE decreased, which proved that the cross‐linked UHMWPE can be prepared by this method. Moreover, there existed different cross‐linked network structures (loose and tight networks) in the samples with the same gel ratio.